Impacto da livre admissão de associados no desempenho de cooperativas de crédito brasileiras - Cinthia Moysés Gonçalves (2022)
Credit unions are financial institutions, incorporated as associations of people, with the objective of satisfying economic, cultural, and social needs and providing financial services to their members. In 2015, to expand the Brazilian credit cooperative movement in an efficient and sustainable way, the National Monetary Council (CMN) issued Resolution No. 4334, which removed some limitations for the constitution and transformation of existing credit unions into free admission credit unions. That is, credit unions that do not require a common bond for membership eligibility as occurs in the case of restricted admission credit unions. Since then, there has been a clear expansion of free admission in Brazil, and thus emerges the interest in evaluating how the adoption of free admission is related to the performance of credit unions. In this sense, the present study aimed to evaluate the impact of the adoption of the Free Admission of members on the economic and financial performance of annual samples of Brazilian singular credit unions from the period between 2016 and 2020. To this end, the research strategy was based on the impact evaluation theory, which sought to highlight whether the performance results of credit unions have a causal relationship with the membership modality. In this context, we sought to capture the effects of free admission through the average treatment effect on the treated (ATT) of 22 PEARLS indicators and the technical efficiency scores obtained through Data Envelopment Analysis (DEA). To this end, the Propensity Score Matching (PSM) was employed, which is the pairing of the two groups (free admission and restricted admission) making them as similar as possible according to observable characteristics (number of members, age of the credit unions, municipal development index, number of inhabitants of the municipalities served, total assets, and affiliation to the systems), except for the membership modality. It was found that, in general, the two groups operate at the same performance level in most indicators. However, it is noteworthy that the free admission presented a superior performance in indicators R6 and R11, which show a better condition of this modality regarding lower operational expenses per average total assets, and higher income from services rendered per administrative expenses. In terms of efficiency, the results indicate that the free admission cooperatives operate with a higher average level of technical efficiency for the entire period, except in 2018, when the efficiency level was similar. The results of this research signal that, in general, the objective of Resolution No. 4334 of 2015 has been achieved, given the expansion of the free admission modality since then, highlighting the superior performance in indicators R6 and R11, and average technical efficiency. Besides evidencing a social inclusion character of this modality of credit unions, which are present in less developed municipalities. However, in general, it is not possible to infer that the type of association generates differences in the performance of cooperatives, since among the 22 indicators only two showed constant differences in performance between free and restricted admission credit unions in the period from 2016 to 2020. Thus, the results provide informational support to assist in managerial decisions of credit unions managers, and to the regulatory agency to advise the promotion of free admission in the Brazilian scenario. Furthermore, this research contributes to the literature on the credit cooperative movement, especially about the impact assessment of policies employed in the cooperative context.